VARIATIONS IN FOOD NORMS AND PRACTICES BY MEAL TIMES AMONG INDIVIDUALS AGED 18-35 IN URBAN INDONESIA: AN ANALYSIS OF THE 2018 INDONESIAN FOOD BAROMETER - Dziljian, Faradiva Tama; Badzlina, Fildzah; Khusun, Helda; Februhartanty, Judhiastuty (Media Gizi Indonesia, 2025)
The culinary history of Indonesia reflects its rich diversity, influenced by cultural, social, and economic factors. In this context, food norms and practices vary across the country, particularly in terms of food selection and consumption. Food norms refer to cultural expectations and rules surrounding food choices, while food practices include the actual behavior of individuals during consumption. This study aimed to identify, analyze, and understand the differences between food norms and practices based on meal times in urban areas of Indonesia. To achieve this objective, a quantitative method with a cross-sectional design was adopted, utilizing data from the 2018 Indonesian Food Barometer (IFB). The study was conducted in 6 provinces- West Java, East Java, South Sulawesi, West Sumatra, Jakarta, and Bali-, with subjects aged 18 to 35 years. Furthermore, the collected data were analyzed using IBM SPSS statistical software and the McNemar Test. The results showed that there were differences between food norms and food practices at breakfast, lunch, and dinner. In particular, the largest gap occurred at breakfast, where food norms tended to be healthier than actual practices. In addition, consumption patterns at dinner showed a greater influence of social factors compared to other meal times.